IMPLEMENTASI MANAJEMEN WAKIL BIDANG KESISWAAN DALAM MENINGKATKAN PRESTASI NON AKADEMIK SISWA DI MTSN LINGGA - Nurisniyati; Syamsul Ridwan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2025)
This study aims to determine how the student affairs viceprincipal improves non-academic achievements at MTs NegeriLingga and to identify the supporting and inhibiting factors ofstudents’ non-academic achievements. This research uses adescriptive qualitative approach. Data collection techniquesinclude interviews, observation, and documentation. The collecteddata was validated using source triangulation, then analyzedthrough data collection, data reduction, data presentation, anddrawing conclusions. The results of the study explain efforts toimprove students’ non-academic achievements. First, planning iscarried out by holding an annual meeting to discuss activities thatmust be prepared to ensure the success of non-academic programs,starting from admission until graduation, as well as assigningmentors according to their respective fields. Second,implementation in the non-academic field is conducted once ortwice a week outside of lesson hours, providing special classes forcoaching based on students’ talents and interests. Third, evaluationin the non-academic field is realized in the form of continuouscoaching. The goal of non-academic programs is to developstudents’ potential, with many students achieving excellence invarious fields, thereby attracting parents and students to enroll atMTsN Lingga. Supporting factors include the involvement ofparents, teachers, mentors, and a positive social environment.Meanwhile, the inhibiting factor is the limited facilities andinfrastructure available at the school.